KARAKTERISTIK SOSIAL YANG MEMPENGARUHI PERSEPSI DAN PERILAKU MASYARAKAT DALAM PENGELOLAAN HUTAN KEMASYARAKATAN - Prihandini Tria Okta Viani; Hari Kaskoyo; Christine Wulandari; Rahmat Safe'i (Tengkawang : Jurnal Ilmu Kehutanan, 2021)
The management area of KPH VIII Batu Tegi which is a watershed of the Way Sekampung watershed included in the priority watershed category because most of the watershed areas have experienced changes in forest function. So that all forms of land management in the region can affect the quality and quantity of the Way Sekampung watershed, including a Social Forestry scheme with community empowerment. Community empowerment in KPH Unit VIII Batu Tegi needs to take into account to aspects of community characteristics that affect its perception and behavior in forest management. This study aimed to analyze the characteristics that influence people's perception and behavior in managing HKm. Respondents in this study were 71 members of the Mandiri Lestari Forest Farmers Group (Gapoktan) who have working areas in the Protected Forest area register 39 Kota Agung Utara. The analytical method used is non parametric statistical correlation Spearman Rank. The instrument used is a Likert scale. The results obtained indicate that the Social characteristics that have a real influence on people's perceptions are age. While the level of community behavior is not influenced by the observed characteristics of the respondents. Keywords : behavior; characteristics; perception, community forest.